Synthesis and antimicrobial studies of hydroxylated chalcone derivatives with variable chain length - Zainab, Ngaini; Siti M., Haris Fadzillah; Hasnain, Hussain (Taylor & Francis, 2012)
A series of (E)-1-(4-alkyloxyphenyl)-3-(hydroxyphenyl)-prop-2-en-1-one have been successfully synthesised via Claisen–Schmidt condensation. The synthesised chalcone derivatives consisted of hydroxyl groups at either ortho, meta or para position and differed in the length of the alkyl groups, CnH2nþ1, where n¼6, 10, 12 and 14. The structures of all compounds were defined by elemental analysis, IR, 1H- and 13C-NMR. The antimicrobial studies were carried out against wild-type Escherichia coli American Type Culture Collection 8739 to evaluate the effect of the hydroxyl and the alkyl groups of the synthesised chalcones. All the synthesised compounds have shown significant antimicrobial activities. The optimum inhibition was dependent on the position of the hydroxyl group as well as the length of the alkyl chains.